Prognostic value of red blood cell distribution width (RDW) in the recurrence of hepatocellular carcinoma following curative resection - Golriz, Mohammad; Ramouz, Ali; Ali-Hasan-Al-Saegh, Sadeq; Shafiei, Saeed; Aminizadeh, Ehsan; Hammad, Ahmed; Mieth, Markus; Rupp, Christian; Springfeld, Christoph; Hoffmann, Katrin; Büchler, Markus W.; Mehrabi, Arianeb (Journal of hepatocellular carcinoma, 2022)
Investigating the prognostic role of pre-and postoperative red blood cell distribution width in hepatocellular carcinoma recurrence after liver resection
Gesehen am 21.12.2022